Postharvest Studies on Carambola (Averrhoa Carambola L.) Fruit - Lam, Peng Fatt (1983)
The carambola (Averrhoa carambola L.) is determined to be anon-climacteric type fruit. The characteristic upsurge of carbon dioxide exhibited by climacteric fruits was not evident in carambola fruits of different ages. Green mature fruit did not respond to 700 ul/l of C2 H4 and 1000 u l/l of ethrel treatment. Unripe fruits (less than 25 % yellow colour) were susceptible to chilling injury after storing for 5 week sat 5 C , but ripe fruits (more than 25 % yellow colour) were not affected. Ripe fruits have a storage life of approximately 9 to 12 week sin 1.5 percent perforated (holes of 5 mm diameter) polyethylene bags. Storage life decreased within creasing storage temperatures from 5°c to ambient temperatures (240 to 35°C). The storage life was 5 weeks at 10° and 15°C:1 to 3 weeks at 20 and ambient temperatures. Unripe fruits in sealed polyethylene bag sat 20°C can be stored for 2 to 3 weeks. They could be stored for another one week when the bags were opened and the fruits exposed to normal air. The fruits would ripen and turn completely yellow in colour.